Pengaruh Promosi Kesehatan dengan Video Interaktif tentang Hypnobirthing terhadap Pengetahuan dan Sikap Ibu Hamil Primigravida dalam Menghadapi Persalinan di PMB Bidan U Kecamatan Pondok Melati Bekasi pada Bulan Juni Tahun 2021 - Dina Arihta Tarigan; Wirdayanti Wirdayanti (Jurnal Health Sains, 2022)
Hypnobirthing is one of the techniques of otohipnosis (self hypnosis), which is an attempt to experience instilling positive intentions / suggestions to the soul / subconscious mind in undergoing pregnancy and preparation for childbirth. The purpose of this study was to find out the effect of health promotion with interactive videos about hypnobirthing on the knowledge and attitudes of pregnant women in the face of childbirth. This type of research uses pre-experimental research methods with pre-post-test designs in one group (One Group Pretest- Posttest Design). The number of samples examined as many as 45 primigravida pregnant women in PMB Midwife U. This study was conducted in June 2021. Data collection techniques using questionnaires. The results of the study based on the results of the T test were the influence of knowledge of pregnant women primigravida before and after being given health promotion with interactive videos about Hypnobirthing with a significant value of 0.001<0.005. With differences before and after the intervention there was an increase in the number of knowledge scores by 1.51. In the attitude of primigravida pregnant women before and after being given interventions about Hypnobirthing with a significant value of 0.001<0.005. With differences before and after health promotion with interactive videos there was an increase in attitude scores of 10.51. It is expected that health workers can provide health promotion about Hypnobirthing periodically with other methods to improve the knowledge and attitude of pregnant women so that they are interested in following and doing Hypnobirthing to feel comfortable, relaxed and safe in undergoing pregnancy and childbirth, especially primigravida pregnant women in the face of childbirth